Foto Estudio Ibis : Sobre la fotografía de pueblo - Antuña, Jesús (2018)
In the following article I propose analyzing the project Foto Estudio Ibis, carried out by Gustavo Frittegotto based on the homonymous photo studio that worked in Arequito (Santa Fe) from the 1930s to 2002. In relation to its archive and Frittegotto’s actions I raise questions about the recovery of photographic archives registered in small communities and the artistic character of these actions.